Scientific Opinion on an application by Dow AgroSciences (EFSA‐GMO‐NL‐2013‐116) for placing on the market of genetically modified insect‐resistant soybean DAS‐81419‐2 for food and feed uses, import and processing under Regulation (EC) No 1829/2003. (5th December 2016) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: Soybean DAS‐81419‐2 was developed by Agrobacterium tumefaciens ‐mediated transformation. It expresses the Cry1F and Cry1Ac proteins to confer resistance to certain lepidopteran species and the PAT protein that confers tolerance to glufosinate ammonium‐based herbicides and that was used as a selectable marker gene. The molecular characterisation of soybean DAS‐81419‐2 did not give rise to safety issues. The agronomic, phenotypic and compositional characteristics of soybean DAS‐81419‐2 tested under field conditions revealed no relevant differences between soybean DAS‐81419‐2 and its conventional counterpart that would give rise to any food and feed or environmental safety concerns. There were no concerns regarding the potential toxicity and allergenicity of the newly expressed proteins Cry1F, Cry1Ac and PAT, and no evidence that the genetic modification might significantly change the overall allergenicity of soybean DAS‐81419‐2. The nutritional value of soybean DAS‐81419‐2 is not expected to differ from that of non‐GM soybean varieties and no post‐market monitoring of food/feed is considered necessary. There are no indications of an increased likelihood of establishment and spread of occasional feral soybean DAS‐81419‐2 plants, unless these plants are exposed to glufosinate ammonium‐based herbicides or infested by insect pests that are susceptible to the Cry1F and Cry1Ac proteins. This will not result in different environmental impacts compared to conventional soybean. Considering the scope of this application, interactions with the biotic and abiotic environment were not considered to be an issue. Risks associated with an unlikely but theoretically possible horizontal gene transfer from soybean DAS‐81419‐2 to bacteria have not been identified. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of soybean DAS‐81419‐2. The GMO Panel concludes that the soybean DAS‐81419‐2 is as safe and as nutritious as its conventional counterpart and the tested non‐GM reference varieties in the context of its scope.